Comprehensive assessment of the functioning of the Krivoy Rog routing network Rog - Горбачов, Петро Федорович; Вдовиченко, Володимир Олексійович; Россолов, Олександр Вікторович; Колій, Олександр Сергійович (Eastern-European Journal of Enterprise Technologies, 2009)
The analysis of existing evaluation approaches of functioning of municipal route network is considered. The method of analysis which takes into account the existing legal standards for the operation route network of cities in Ukraine is offered, results of analysis of the functioning of the route network of Krivoy Rog are given